The historical mind humanistic renewal in a post-constitutional age - Garrison, Justin D.; Holston, Ryan R. (State University of New York Press, 2020)
"Timely and provocative assessment of various cultural, moral, and political problems in "post-constitutional" America"--
Keywords: Ideengeschichte; Politische Philosophie; Verfassung; Humanismus; USA; Political science / Philosophy; Constitutional law / Philosophy; Constitutional law / United States; Humanism / United States; United States / Politics and government / Philosophy; Constitutional law; Humanism; Politics and government; United States; Aufsatzsammlung